2023
DOI: 10.35445/alishlah.v15i1.2459
|View full text |Cite
|
Sign up to set email alerts
|

Developing Students’ Worksheets based on the Inquiry-Flipped Classroom Learning Model to Improve Argumentation Skills

Abstract: This study aims to develop students’ worksheets (LKPD) by the syntax of the inquiry-flipped classroom model to improve argumentation skills using the ADDIE development model (analysis, design, development, implementation, and evaluation). In blended learning, the teacher provides material through several platforms that support online learning. Accordingly, we need an LKPD to help students understand the material independently and improve students' argumentation skills. The research data was acquired by distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
0
0
Order By: Relevance
“…The results of the V'aiken validity test are as follows, an average of 0.92 on the material aspect, 0.96 on the media aspect, and 0.83 on the language aspect, all of which are in the very valid category. Similar research by Epinur & Minarni (2023) and Ramadani et al (2023) shows that worksheets on the inquiry-flipped classroom have very valid validity criteria. So, it can be concluded that the thermochemistry e-worksheet based on FGIL is very valid in terms of material, media, and language aspects so it is suitable for use in teaching thermochemistry material.…”
Section: Discussionsupporting
confidence: 55%
“…The results of the V'aiken validity test are as follows, an average of 0.92 on the material aspect, 0.96 on the media aspect, and 0.83 on the language aspect, all of which are in the very valid category. Similar research by Epinur & Minarni (2023) and Ramadani et al (2023) shows that worksheets on the inquiry-flipped classroom have very valid validity criteria. So, it can be concluded that the thermochemistry e-worksheet based on FGIL is very valid in terms of material, media, and language aspects so it is suitable for use in teaching thermochemistry material.…”
Section: Discussionsupporting
confidence: 55%